Neurovisceral integration in cardiac and emotional regulation. - Thayer, J.F (IEEE Engineering in medicine and biology magazine)
The utility of heart-rate variability (HRV) to index important aspects of neural control of the heart has made it one of the most valuable tools for researchers interested in health and behavior. However, most of the literature and extant data on the central origins of HRV have been derived from animal models. As yet little is known about the central nervous system (CNS) origins and concomitants in humans. In the following we will briefly detail a set of neural structures that have been associated with important CNS functions including cardiac regulation and emotional regulation. We will briefly summarize recent data using pharmacological, neuroimaging, and psychophysiological techniques that have examined CNS concomitants of HRV especially during emotion. Based on these and other data will we report the results of a computational model that examined the interactions of several neural structures and their effect on emotion-related HRV.